Innovated Solutions For Automated Charging And Stoking - J. Dienenthal (The Southern African Institute of Mining and Metallurgy, 2007)
Automatic Charging and Stoking Machines for use at ferroalloy furnaces are in operation for more than 20years. Dango & Dienenthal Maschinenbau GmbH (short: DDS) has developed several machine generations. Today advanced solutions help to achieve better charging and stoking results to minimize cost and to improve the working environment around the furnaces. Three different alternatives can be considered: Rail-mounted solution The machine(s) travel(s) on an overhead monorail to one or several furnaces and is locked in the desired working position from where charging and stoking is performed. Mobile solution This machine travels on the charging platform and is also locked at the respective working position to perform charging and stoking. Automation of a standard mobile charging and stoking machine A standard charging and stoking machine can be adapted for automation. A reliable navigation system is included. Charging and stoking is performed with the moving machine. Advantage versus other solutions: considerable lower investment cost and possibility to upgrade the mobile charging and stoking machine for later automation. Overall, automatic charging and stoking can save up to 10 per cent of the specific smelting energy. A better and more consistent furnace operation can be achieved. Different programs are used to cope with different furnace conditions and changing raw materials. All machine movements can be recorded and correlated to other furnace parameters. Working environment on the charging platform is greatly improved.